A PET plastic bottle blank and molding process
By adding raw materials such as PPSU resin and modified graphene microsheets to PET plastic bottle preforms, the problem of poor wear resistance of PET plastic bottle preforms is solved, and the effect of improving tensile strength, wear resistance and barrier properties is achieved, meeting the market demand for high-performance plastic bottle preforms.
Patent Information
- Application Number
- CN202411718450.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The wear resistance of existing PET plastic bottle preforms is poor, which leads to easy wear during use, affecting the stability of use.
Based on PET resin, PPSU resin, modified graphene microsheets, compatibility agents, antioxidants, antibacterial agents and lubricants are added. Through the mutual cooperation between the raw materials, the heat resistance, chemical corrosion resistance and oxygen resistance of the plastic bottle preform are enhanced, and the tensile strength and barrier properties are improved by modifying graphene microsheets.
The tensile strength, wear resistance and barrier properties of PET plastic bottle preforms are improved, the wear amount and oxygen transmission are reduced, and the plastic bottle preforms have the advantages of good light transmittance, high tensile strength, strong wear resistance and high barrier properties, meeting market demand.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polymer compound compositions, and more specifically, to a PET plastic bottle blank and a molding process. Background Art
[0002] Plastic bottles are a common packaging material in daily life, and are often used in mineral water bottles, beverage bottles, cosmetic bottles, medicinal packaging bottles, etc. Plastic bottles are generally made of plastic bottle blanks and are blow-molded. The plastic bottle blanks currently on the market are usually made of PET, PP, PE, PVA, etc. For PET plastic bottle blanks, the raw material is PET resin, which is polyethylene terephthalate. The wear resistance of plastic bottle blanks refers to the ability of plastic bottle blanks to resist wear caused by friction. Improving the wear resistance of plastic bottle blanks is conducive to improving the wear resistance of plastic bottles, thereby reducing the wear of plastic bottles during use, which is of great significance for improving the stability of plastic bottles. However, the wear resistance of PET plastic bottle blanks currently on the market is slightly poor and needs to be further improved. Summary of the invention
[0003] In order to reduce the wear amount of PET plastic bottle preforms and improve the wear resistance of PET plastic bottle preforms, the present application provides a PET plastic bottle preform and a molding process.
[0004] In the first aspect, the present application provides a PET plastic bottle blank, which adopts the following technical solution:
[0005] A PET plastic bottle blank is mainly made of the following raw materials in parts by weight: 75-85 parts of PET resin, 15-25 parts of PPSU resin, 2-4 parts of modified graphene microsheets, 0.5-1.5 parts of a compatibilizer, 0.2-0.5 parts of an antioxidant, 0.1-0.3 parts of an antibacterial agent, and 0.1-0.3 parts of a lubricant; the modified graphene microsheets are obtained by treating the graphene microsheets with tetraethyl orthosilicate, 3-trimethoxysilane acrylate, chitosan, and 4-n-butylaniline.
[0006] The PET plastic bottle blank of the present application has a tensile strength of more than 67MPa, a wear amount of less than 5mg / 100r, and an oxygen permeability of less than 3×10 -5 cm 3 / (m 2 ·d·Pa), light transmittance>82%, which makes the plastic bottle preform have the advantages of good light transmittance, high tensile strength, strong wear resistance and high barrier property, meeting the market demand.
[0007] The raw materials of plastic bottle blanks are based on PET resin, and PPSU resin is added to the raw materials. The cooperation between them is used to enhance the heat resistance and chemical corrosion resistance, so that it can remain stable at higher temperatures. Compatibilizers are added to the raw materials to improve the compatibility of PET resin and PPSU resin and increase the interaction between the two. Antioxidants, antibacterial agents, and lubricants are added to the raw materials to keep the plastic bottle blanks with good antioxidant, antibacterial, and processability, and extend the service life. Modified graphene microflakes are added to the raw materials, silicon dioxide is formed on the graphene microflakes by using tetraethyl orthosilicate, 3-trimethoxysilane acrylate, chitosan, and 4-n-butylaniline are further grafted, and ester groups, siloxy groups, phenyl groups, and hydroxyl groups are introduced to increase the amount of surface active groups and branched chains of the modified graphene microflakes, improve the dispersibility, compatibility, and interface bonding strength of the modified graphene microflakes, form a cross-linked network in the raw materials, increase the cross-linking density and integrity, improve the tensile strength of the plastic bottle preform, further reduce the wear and oxygen permeability of the plastic bottle preform, and make the plastic bottle preform exhibit better comprehensive performance.
[0008] Optionally, the modified graphene microsheet is prepared by the following method:
[0009] T1, mixing ethanol aqueous solution and graphene microsheets, adjusting the pH value to 3-4, adding ethyl orthosilicate ethanol solution dropwise, the addition time of ethyl orthosilicate ethanol solution is 40-80min, after the addition is completed, stirring is continued for 4-6h, filtering, drying, and calcining to obtain silicon-containing graphene microsheets;
[0010] T2. Mix ethanol and silicon-containing graphene microsheets, heat to 50-70°C, add 3-trimethoxysilane acrylate, stir for 2-4 hours, then add emulsifier and mix, then add chitosan and 4-n-butylaniline, stir for 4-6 hours, filter, wash, and dry to obtain modified graphene microsheets.
[0011] Optionally, the weight ratio of the graphene microsheets, tetraethyl orthosilicate ethanol solution, 3-trimethoxysilane acrylate, chitosan, and 4-n-butylaniline is 10:(44-66):(1-3):(0.5-1.5):(0.3-0.7), and the weight ratio of ethanol and tetraethyl orthosilicate in the tetraethyl orthosilicate ethanol solution is 10:(0.5-1.5).
[0012] By adopting the above technical scheme, the hydrolysis of tetraethyl orthosilicate in water is combined with calcination to load silicon dioxide on the graphene microsheets to obtain silicon-containing graphene microsheets. In addition, a tetraethyl orthosilicate ethanol solution is prepared in advance, and the tetraethyl orthosilicate is dispersed in the ethanol solution, and then dispersed in water to fully disperse the tetraethyl orthosilicate, and then the addition method of dripping is combined to increase the dispersion uniformity of silicon dioxide on the graphene microsheets, and improve the interaction between the graphene microsheets and silicon dioxide.
[0013] In addition, 3-trimethoxysilane acrylate is grafted on the surface of silicon-containing graphene microsheets using siloxy groups to introduce ester groups, siloxy groups, and carbon-carbon double bonds. Then, chitosan and 4-n-butylaniline are grafted using the reaction between carbon-carbon double bonds and amine groups, and phenyl and hydroxyl groups are introduced, thereby increasing the amount of active groups on the surface of the modified graphene microsheets and the amount of surface branches of the modified graphene microsheets, thereby improving the dispersibility, bonding strength, and compatibility of the modified graphene microsheets, thereby improving the tensile strength, wear resistance, and barrier properties of the plastic bottle blanks, and making the modified graphene microsheets exhibit better use effects.
[0014] Optionally, the weight ratio of the graphene microsheets to the emulsifier is 10:(0.3-0.7).
[0015] By adopting the above technical solution, the weight ratio of graphene microsheets and emulsifier is optimized, the amount of emulsifier added is controlled, and the full mixing of the raw materials is facilitated.
[0016] Optionally, the emulsifier is one or more of Span 80, Span 60, Span 40, Tween 80, Tween 60, and Tween 40.
[0017] By adopting the above technical solution, the emulsifier is optimized, which is convenient for the selection of the emulsifier. Moreover, the emulsifier can make the raw materials fully contact and react, ensure the stability and quality of the preparation of the modified graphene microsheets, improve the use effect of the modified graphene microsheets, enhance the tensile strength of the plastic bottle blank, and reduce the wear and oxygen permeability of the plastic bottle blank, so that the plastic bottle blank exhibits better comprehensive performance.
[0018] Optionally, the emulsifier is Span 80 and Tween 80, and the weight ratio of Span 80 to Tween 80 is (1-3):(1-3). In multiple embodiments, the weight ratio of Span 80 to Tween 80 is 2:1, and the weight ratio can also be set to 1:1, 1:2, 1:3, 2:3, 3:1, 3:2 as needed, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0019] Optionally, the weight ratio of the graphene microsheets, the ethanol aqueous solution, and ethanol is 1:(7-13):(7-13), and the mass concentration of ethanol in the ethanol aqueous solution is 30-50%.
[0020] By adopting the above technical scheme, the weight ratio of graphene microsheets, ethanol aqueous solution, and ethanol is optimized, so that the graphene microsheets are dispersed in the ethanol aqueous solution, and the silicon-containing graphene microsheets are dispersed in the ethanol, so as to ensure the stability of the preparation of modified graphene microsheets. In multiple implementation schemes, the weight ratio of graphene microsheets, ethanol aqueous solution, and ethanol is 1:10:10, and the mass concentration of ethanol in the ethanol aqueous solution is 40%. The weight ratio can also be set to 1:7:7, 1:7:10, 1:7:13, 1:10:7, 1:10:13, 1:13:7, 1:13:10, 1:13:13 as needed. The mass concentration of ethanol can also be set to 30%, 35%, 45%, 50% as needed, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] Optionally, in the calcination treatment of step T1, inert gas protection is adopted, and the calcination temperature is 550-650° C. and the time is 1-3 hours.
[0022] By adopting the above technical solution, the calcination temperature and time are optimized, which is convenient for calcination. During the calcination process, the bonding strength between silicon dioxide and graphene microsheets is effectively increased to ensure the stability of silicon-containing graphene microsheets. In addition, inert gas protection is also used during the calcination process to effectively prevent the graphene microsheets from being oxidized and ensure the stability of the calcination.
[0023] Optionally, in the pH adjustment of step T1, a hydrochloric acid aqueous solution is used to adjust the pH, and the mass concentration of hydrochloric acid in the hydrochloric acid aqueous solution is 5-10%.
[0024] By adopting the above technical solution, the pH value is adjusted using hydrochloric acid aqueous solution, which is convenient for controlling the pH value of the reaction system, and the hydrochloric acid aqueous solution is abundant in source and cheap. In multiple embodiments, the mass concentration of hydrochloric acid in the hydrochloric acid aqueous solution is 8%, and the mass concentration of hydrochloric acid can also be set to 5%, 6%, 7%, 9%, 10% as required, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0025] Optionally, the graphene microsheets have an average radial width of 1-20 μm and an average thickness of 5-25 nm.
[0026] By adopting the above technical solution, the graphene microsheets are optimized to ensure the stability of the source of graphene microsheets, and the dispersibility of the modified graphene microsheets can be increased, the use effect of the modified graphene microsheets can be improved, and the quality of the plastic bottle blanks can be ensured. In multiple embodiments, the average radial width of the graphene microsheets is 15 μm and the average thickness is 13 nm. The average radial width can also be set to 1 μm, 5 μm, 10 μm, 20 μm as needed, and the average thickness can also be set to 5 nm, 10 nm, 15 nm, 20 nm, 25 nm as needed, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0027] Optionally, the compatibilizer is an ethylene-acrylate-glycidyl methacrylate terpolymer;
[0028] The antioxidant is one or more of antioxidant 168, antioxidant 330, antioxidant 1010, antioxidant 2246, and antioxidant 1035.
[0029] By adopting the above technical solution, the compatibilizer and antioxidant are optimized, which facilitates the selection of the compatibilizer and antioxidant. Moreover, the compatibilizer can improve the compatibility between the PET resin and the PPSU resin and enhance the integrity, while the antioxidant can inhibit the oxidative degradation during processing and use, extend the service life, and ensure the stability and reliability of the plastic bottle blank.
[0030] Optionally, the antioxidants are two kinds of antioxidants, namely, antioxidant 168 and antioxidant 2246, and the weight ratio of antioxidant 168 to antioxidant 2246 is (1-3):(1-3). In multiple embodiments, the weight ratio of antioxidant 168 to antioxidant 2246 is 1:1, and the weight ratio can also be set to 1:2, 1:3, 2:1, 2:3, 3:1, 3:2 as needed, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0031] Optionally, the antibacterial agent is one or more of nano zinc oxide, nano copper oxide, nano silver, zeolite-loaded zinc, and zeolite-loaded copper;
[0032] The lubricant is one or more of N,N-ethylene bisstearamide, ethylene bisstearic acid amide, pentaerythritol stearate, and glyceryl stearate.
[0033] By adopting the above technical solution, the antimicrobial agent and lubricant are optimized, which facilitates the selection of the antimicrobial agent and lubricant. The antimicrobial agent can effectively inhibit the growth of microorganisms, improve the antimicrobial property, and extend the service life. The lubricant can reduce the friction resistance of the plastic bottle blank during processing, improve the fluidity, facilitate molding, and ensure the quality of the plastic bottle blank.
[0034] In the second aspect, the present application provides a molding process of a PET plastic bottle blank, which adopts the following technical solution:
[0035] A molding process of a PET plastic bottle blank mainly comprises the following steps:
[0036] S1, mixing PET resin, PPSU resin, modified graphene microsheets, compatibilizer, antioxidant, antibacterial agent, and lubricant, and drying to obtain a plastic mixture;
[0037] S2, heating and melting the plastic mixture, extruding and granulating, and obtaining plastic masterbatch;
[0038] S3, injection molding the plastic masterbatch, cooling and demoulding, to obtain a plastic bottle blank.
[0039] By adopting the technical solution, the preparation of plastic bottle blanks is facilitated.
[0040] Optionally, in the preparation of the plastic masterbatch in step S2, a twin-screw extruder is used to prepare the plastic masterbatch, and the screw speed is 230-270r / min, and the heating and melting temperature is divided into ten zones, and the temperatures of zones one to ten are 235-245°C, 245-255°C, 255-265°C, 265-275°C, 275-285°C, 275-285°C, 280-290°C, 280-290°C, 285-295°C, and 285-295°C, respectively.
[0041] By adopting the above technical solution, the heating and melting temperature is optimized, so that the plastic mixture can be fully melted and the uniformity of the mixture can be increased. In addition, the heating is carried out in a gradual heating manner, and the temperature gradient of each area is reasonably set to facilitate heat transfer, reduce the occurrence of local overheating, and ensure the stability of plastic masterbatch preparation.
[0042] In multiple embodiments, in the preparation of plastic masterbatch in step S2, the screw speed is 250r / min, and the screw speed can also be set to 230r / min, 240r / min, 260r / min, 270r / min as needed, but it is not limited to the listed values, and other values not listed in the numerical range are also applicable. In multiple embodiments, in the preparation of plastic masterbatch in step S2, the temperatures of zones one to ten are 240°C, 250°C, 260°C, 270°C, 280°C, 280°C, 285°C, 285°C, 290°C, 290°C, respectively, but it is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0043] Optionally, in the injection molding of step S3, the injection molding temperature is 280-300°C.
[0044] By adopting the above technical solution, the injection molding temperature is optimized, which facilitates the full melting of the plastic masterbatch, improves the fluidity of the molten plastic masterbatch, makes the injection molding process more stable, and ensures the size and surface quality of the plastic bottle blank. In multiple embodiments, in the injection molding of step S3, the injection molding temperature is 290°C, and the temperature can also be set to 280°C, 285°C, 295°C, 300°C as needed, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0045] In summary, this application has at least the following beneficial effects:
[0046] The PET plastic bottle blank of the present application is based on PET resin, and PPSU resin is added to the raw material to increase heat resistance and chemical corrosion resistance. Modified graphene microsheets are also added to the raw material, and silicon dioxide is formed on the graphene microsheets using tetraethyl orthosilicate, and then 3-trimethoxysilane acrylate is grafted using siloxy groups, and then chitosan and 4-n-butylaniline are grafted using the reaction between amine groups and carbon-carbon double bonds, so that the surface of the modified graphene microsheet contains a large number of active groups such as ester groups, siloxy groups, phenyl groups, and hydroxyl groups, thereby improving the dispersibility, compatibility, and interfacial bonding of the modified graphene microsheets, and forming a cross-linked network in the raw material to increase the cross-linking density and integrity, thereby improving the tensile strength of the plastic bottle blank, reducing the wear and oxygen permeability, and making the tensile strength of the plastic bottle blank greater than 67MPa, the wear less than 5mg / 100r, and the oxygen permeability less than 3×10 -5 cm 3 / (m 2 ·d·Pa), light transmittance>82%, which makes the plastic bottle preform have the advantages of good light transmittance, high tensile strength, strong wear resistance, high barrier property, and show better comprehensive performance to meet market demand. DETAILED DESCRIPTION
[0047] The present application is further described in detail below with reference to the embodiments.
[0048] Preparation Example
[0049] Preparation Example 1
[0050] A modified graphene microsheet is prepared by the following method:
[0051] T1. At a speed of 300r / min, add 10g of graphene microsheets to 100g of 40% ethanol aqueous solution, and stir for 10min. Use 8% hydrochloric acid aqueous solution to adjust the pH value to 3.5, add 55g of ethyl orthosilicate ethanol solution, and the addition time of ethyl orthosilicate ethanol solution is 60min. After the addition is completed, continue stirring for 5h. Then filter and dry. After that, calcine for 2h under nitrogen protection at a temperature of 600℃ to obtain silicon-containing graphene microsheets.
[0052] Among them, the average radial width of the graphene microsheets is 15μm, the average thickness is 13nm, and they are selected from Xiamen Kaina Graphene Technology Co., Ltd.; the ethanol solution of tetraethyl orthosilicate is a mixture of ethanol and tetraethyl orthosilicate, and the weight ratio of ethanol to tetraethyl orthosilicate is 10:1.
[0053] T2. Add the silicon-containing graphene microsheets obtained in step T1 to 100g of ethanol at a speed of 300r / min, and stir for 10min. Heat to 60°C, add 2g of 3-trimethoxysilane acrylate, and stir for 3h. Then add 0.5g of emulsifier and stir for 3min. Then add 1g of chitosan and 0.5g of 4-n-butylaniline and stir for 5h. Then filter, wash three times with ethanol, using 50g of ethanol each time, and dry to obtain modified graphene microsheets.
[0054] Among them, the emulsifiers are Span 80 and Tween 80, and the weight ratio of Span 80 to Tween 80 is 2:1.
[0055] Preparation Example 2
[0056] A modified graphene microsheet is prepared by the following method:
[0057] T1. At a speed of 300r / min, add 10g of graphene microsheets to 100g of 40% ethanol aqueous solution, and stir for 10min. Use 8% hydrochloric acid aqueous solution to adjust the pH value to 3, add 44g of ethyl orthosilicate ethanol solution, and the addition time of ethyl orthosilicate ethanol solution is 40min. After the addition is completed, continue stirring for 4h. Then filter and dry. After that, calcine for 3h under nitrogen protection at a temperature of 550℃ to obtain silicon-containing graphene microsheets.
[0058] Among them, the average radial width of the graphene microsheets is 15μm, the average thickness is 13nm, and they are selected from Xiamen Kaina Graphene Technology Co., Ltd.; the ethanol solution of tetraethyl orthosilicate is a mixture of ethanol and tetraethyl orthosilicate, and the weight ratio of ethanol to tetraethyl orthosilicate is 10:1.
[0059] T2. Add the silicon-containing graphene microsheets obtained in step T1 to 100g of ethanol at a speed of 300r / min and stir for 10min. Heat to 70°C, add 1g of 3-trimethoxysilane acrylate, and stir for 2h. Then add 0.7g of emulsifier and stir for 3min. Then add 1.5g of chitosan and 0.3g of 4-n-butylaniline and stir for 4h. Then filter, wash three times with ethanol, using 50g of ethanol each time, and dry to obtain modified graphene microsheets.
[0060] Among them, the emulsifiers are Span 80 and Tween 80, and the weight ratio of Span 80 to Tween 80 is 2:1.
[0061] Preparation Example 3
[0062] A modified graphene microsheet is prepared by the following method:
[0063] T1. At a speed of 300r / min, add 10g of graphene microsheets to 100g of 40% ethanol aqueous solution, and stir for 10min. Use 8% hydrochloric acid aqueous solution to adjust the pH value to 4, add 66g of ethyl orthosilicate ethanol solution, and the addition time of ethyl orthosilicate ethanol solution is 80min. After the addition is completed, continue stirring for 6h. Then filter and dry. After that, calcine for 1h under nitrogen protection at a temperature of 650℃ to obtain silicon-containing graphene microsheets.
[0064] Among them, the average radial width of the graphene microsheets is 15μm, the average thickness is 13nm, and they are selected from Xiamen Kaina Graphene Technology Co., Ltd.; the ethanol solution of tetraethyl orthosilicate is a mixture of ethanol and tetraethyl orthosilicate, and the weight ratio of ethanol to tetraethyl orthosilicate is 10:1.
[0065] T2. Add the silicon-containing graphene microsheets obtained in step T1 to 100g of ethanol at a speed of 300r / min and stir for 10min. Heat to 50°C, add 3g of 3-trimethoxysilane acrylate, and stir for 4h. Then add 0.3g of emulsifier and stir for 3min. Then add 0.5g of chitosan and 0.7g of 4-n-butylaniline and stir for 6h. Then filter, wash three times with ethanol, using 50g of ethanol each time, and dry to obtain modified graphene microsheets.
[0066] Among them, the emulsifiers are Span 80 and Tween 80, and the weight ratio of Span 80 to Tween 80 is 2:1.
[0067] Example
[0068] Table 1 Raw material dosage of plastic bottle blank (unit: kg)
[0069]
[0070] Example 1
[0071] A PET plastic bottle blank, the raw materials and raw material ratios of which are shown in Table 1.
[0072] Among them, the PET resin is PET CR8863; the PPSU resin is PPSU P3010; the modified graphene microsheets are prepared by the method of Preparation Example 1; the compatibilizer is ethylene-acrylate-glycidyl methacrylate terpolymer, specifically compatibilizer AX8900; the antioxidants are antioxidant 168 and antioxidant 2246, and the weight ratio of antioxidant 168 to antioxidant 2246 is 1:1; the antibacterial agent is nano zinc oxide with an average particle size of 20 nm, and is selected from Hangzhou Jikang New Materials Co., Ltd.; the lubricant is N,N-ethylene bisstearamide.
[0073] A molding process for a PET plastic bottle blank mainly comprises the following steps:
[0074] S1. Add PPSU resin, modified graphene microsheets, compatibilizer, antioxidant, antibacterial agent and lubricant to PET resin, stir for 5 minutes, and dry to obtain a plastic mixture.
[0075] S2. Put the plastic mixture into a twin-screw extruder, heat and melt it, extrude it into granules, and obtain plastic masterbatch.
[0076] Among them, the heating and melting temperature is divided into ten zones, and the temperatures of zones one to ten are 240°C, 250°C, 260°C, 270°C, 280°C, 280°C, 285°C, 285°C, 290°C, and 290°C respectively, and the screw speed of the twin-screw extruder is 250r / min.
[0077] S3, putting the plastic masterbatch into the injection molding machine, injection molding, cooling and demoulding, and obtaining the plastic bottle blank.
[0078] The injection molding temperature is 290°C.
[0079] Example 2
[0080] A PET plastic bottle blank, which is different from Example 1 in that the raw material ratio of the plastic bottle blank is different, and the raw material ratio of the plastic bottle blank is shown in Table 1.
[0081] Example 3
[0082] A PET plastic bottle blank, which is different from Example 1 in that the raw material ratio of the plastic bottle blank is different, and the raw material ratio of the plastic bottle blank is shown in Table 1.
[0083] Example 4
[0084] A PET plastic bottle blank, which differs from Example 1 in that the source of the modified graphene microflakes in the raw materials of the plastic bottle blank is different, and the modified graphene microflakes are prepared by the method of Preparation Example 2.
[0085] Example 5
[0086] A PET plastic bottle blank, which differs from Example 1 in that the source of the modified graphene microflakes in the raw materials of the plastic bottle blank is different, and the modified graphene microflakes are prepared by the method of Preparation Example 3.
[0087] Comparative Example
[0088] Comparative Example 1
[0089] A PET plastic bottle blank, which differs from Example 1 in that an equal amount of graphene microsheets are used to replace modified graphene microsheets in the raw materials of the plastic bottle blank.
[0090] Comparative Example 2
[0091] A PET plastic bottle blank, which differs from Example 1 in that, in the raw materials of the plastic bottle blank, an equal amount of silicon dioxide is used to replace the modified graphene microsheets, and the average particle size of the silicon dioxide is 2 μm, and the silicon dioxide is selected from Jiangsu Jingshengyuan New Material Technology Co., Ltd.
[0092] Comparative Example 3
[0093] A PET plastic bottle blank, which differs from Example 1 in that, in the raw materials of the plastic bottle blank, the modified graphene microsheets are replaced with equal amounts of graphene microsheets and silicon dioxide, and the weight ratio of the graphene microsheets to the silicon dioxide is 10:1.4, and the average particle size of the silicon dioxide is 2 μm, and is selected from Jiangsu Jingshengyuan New Material Technology Co., Ltd.
[0094] Comparative Example 4
[0095] A PET plastic bottle blank, which differs from Example 1 in that, in the raw materials of the plastic bottle blank, an equal amount of silicon-containing graphene microsheets are used to replace the modified graphene microsheets, and the silicon-containing graphene microsheets are prepared by the method of step T1 of Preparation Example 1.
[0096] Comparative Example 5
[0097] A PET plastic bottle blank, which differs from Example 1 in that in the raw materials of the plastic bottle blank, in the preparation method of the modified graphene microsheets, an equal amount of 3-trimethoxysilane propyl acrylate is used to replace chitosan and 4-n-butylaniline.
[0098] Comparative Example 6
[0099] A PET plastic bottle blank, which differs from Example 1 in that, in the raw materials of the plastic bottle blank, an equal amount of chitosan is used to replace 4-n-butylaniline in the preparation method of the modified graphene microsheets.
[0100] Comparative Example 7
[0101] A PET plastic bottle blank, which differs from Example 1 in that, in the raw materials of the plastic bottle blank, an equal amount of 4-n-butylaniline is used to replace chitosan in the preparation method of the modified graphene microsheets.
[0102] Performance Testing
[0103] (1) The plastic bottle preforms obtained in Examples 1 to 5 were respectively taken, and the total migration amount, potassium permanganate consumption, heavy metal (Pb) content, etc. of the plastic bottle preforms were tested in accordance with GB4806.7-20016 "National Food Safety Standard for Plastic Materials and Products for Food Contact", BB / T0060-2012 "Polyethylene Terephthalate (PET) Bottle Preforms for Packaging Containers", and GB13113-1991 "Sanitary Standard for Polyethylene Terephthalate Molded Products for Food Containers and Packaging Materials".
[0104] After testing, the total migration amount of the plastic bottle blanks obtained in Examples 1-5 is ≤5 mg / dm 2 , potassium permanganate consumption ≤5mg / kg, heavy metal (as Pb) content ≤0.5mg / kg, antimony (as Sb) content ≤0.03mg / kg, acetaldehyde content ≤5g / g, with good safety.
[0105] (2) The plastic bottle preforms obtained in Examples 1-5 and Comparative Examples 1-7 were respectively taken and the following performance tests were performed on the plastic bottle preforms. The test results are shown in Table 2.
[0106] Among them, tensile strength performance test: According to GB / T1040.1-2018 "Determination of tensile properties of plastics Part 1: General principles", the tensile strength of plastic bottle preforms is tested.
[0107] Wear resistance test: According to GB / T5478-2008 "Plastic rolling wear test method", the wear amount of plastic bottle embryo is tested.
[0108] Barrier performance test: According to GB / T1038-2000 "Plastic film and sheet gas permeability test method pressure difference method", the oxygen permeability of plastic bottle preforms at a relative humidity of 60% was tested.
[0109] Light transmittance performance test: According to GB / T2410-2008 "Determination of light transmittance and haze of transparent plastics", the light transmittance of plastic bottle preforms is tested.
[0110] Table 2 Test results
[0111]
[0112] As can be seen from Table 2, the plastic bottle blank of the present application has a higher tensile strength of 67.23-68.96 MPa, which makes it show higher mechanical properties. It also has lower wear and oxygen permeability, with a wear of 3.3-4.6 mg / 100r and an oxygen permeability of (1.93-2.31)×10 -5 cm 3 / (m 2 ·d·Pa), making it show higher wear resistance and barrier properties. At the same time, it also maintains good light transmittance, which is 82.6-82.9%. The plastic bottle blank of the present application has the advantages of good light transmittance, high tensile strength, strong wear resistance and high barrier properties through the mutual cooperation between the raw materials, and has good comprehensive performance to meet market demand.
[0113] Comparative Examples 1-4 are compared. In Comparative Example 1, graphene microflakes are added to the raw materials of the plastic bottle blank; in Comparative Example 2, silicon dioxide is added to the raw materials of the plastic bottle blank; in Comparative Example 3, graphene microflakes and silicon dioxide are added to the raw materials of the plastic bottle blank. It can be seen that adding graphene microflakes and silicon dioxide to the raw materials at the same time does not basically affect the light transmittance, but the synergistic effect between the two can increase the tensile strength and reduce the wear and oxygen permeation. Combined with Comparative Example 4, silicon-containing graphene microflakes are added to the raw materials of the plastic bottle blank in Comparative Example 4, that is, silicon dioxide-loaded graphene microflakes. It can be seen that loading silicon dioxide on graphene microflakes can improve the interaction between silicon dioxide and graphene microflakes. Combined with Example 1, modified graphene microflakes are added to the raw materials of the plastic bottle blank in Example 1, and the graphene microflakes are obtained by treating silicon-containing graphene microflakes with 3-trimethoxysilane acrylate, chitosan, and 4-n-butylaniline. It can be seen from this that modifying the silicon-containing graphene microsheets and increasing the number of surface active groups on the silicon-containing graphene microsheets can further improve the tensile strength, wear resistance and barrier properties, making the plastic bottle preform exhibit better overall performance.
[0114] Example 1 is compared with comparative examples 5-7. The modified graphene microsheet of comparative example 5 is obtained by treating silicon-containing graphene microsheets with 3-trimethoxysilane acrylate; the modified graphene microsheet of comparative example 6 is obtained by treating silicon-containing graphene microsheets with 3-trimethoxysilane acrylate and chitosan; the modified graphene microsheet of comparative example 7 is obtained by treating silicon-containing graphene microsheets with 3-trimethoxysilane acrylate and 4-n-butylaniline; the modified graphene microsheet of example 1 is obtained by treating silicon-containing graphene microsheets with 3-trimethoxysilane acrylate, chitosan, and 4-n-butylaniline. It can be seen from this that on the basis of loading silica on graphene microsheets, 3-trimethoxysilane acrylate is further used for grafting, and then chitosan and 4-n-butylaniline are grafted to introduce active groups such as siloxy, phenyl, and hydroxyl groups on the surface of silicon-containing graphene microsheets. This can improve the dispersibility of the modified graphene microsheets and increase the interface bonding strength between them and the raw materials. It can also form a cross-linked network, increase the cross-linking density and integrity, improve tensile strength, reduce wear and oxygen permeability, and make the plastic bottle preform have better mechanical properties, wear resistance and barrier properties.
[0115] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A PET plastic bottle blank, characterized in that: The plastic bottle blank is mainly made of the following raw materials in parts by weight: 75-85 parts of PET resin, 15-25 parts of PPSU resin, 2-4 parts of modified graphene microsheets, 0.5-1.5 parts of compatibilizer, 0.2-0.5 parts of antioxidant, 0.1-0.3 parts of antibacterial agent, and 0.1-0.3 parts of lubricant; the modified graphene microsheets are obtained by treating the graphene microsheets with tetraethyl orthosilicate, 3-trimethoxysilane acrylate, chitosan, and 4-n-butylaniline; The modified graphene microsheet is prepared by the following method: T1, mixing ethanol aqueous solution and graphene microsheets, adjusting the pH value to 3-4, adding ethyl orthosilicate ethanol solution dropwise, the addition time of ethyl orthosilicate ethanol solution is 40-80min, after the addition is completed, stirring is continued for 4-6h, filtering, drying, and calcining to obtain silicon-containing graphene microsheets; T2, mixing ethanol and silicon-containing graphene microsheets, heating to 50-70°C, adding 3-trimethoxysilane acrylate, stirring for 2-4 hours, then adding an emulsifier and mixing, then adding chitosan and 4-n-butylaniline, stirring for 4-6 hours, filtering, washing, and drying to obtain modified graphene microsheets; The weight ratio of the graphene microsheets, tetraethyl orthosilicate ethanol solution, 3-trimethoxysilane acrylate, chitosan, and 4-n-butylaniline is 10:(44-66):(1-3):(0.5-1.5):(0.3-0.7), and the weight ratio of ethanol to tetraethyl orthosilicate in the tetraethyl orthosilicate ethanol solution is 10:(0.5-1.5); The weight ratio of the graphene microsheets to the emulsifier is 10:(0.3-0.7).
2. A PET plastic bottle preform according to claim 1, characterized in that: The emulsifier is one or more of Span 80, Span 60, Span 40, Tween 80, Tween 60 and Tween 40.
3. A PET plastic bottle blank according to claim 1, characterized in that: In the calcination treatment of step T1, inert gas protection is adopted, and the calcination temperature is 550-650° C. and the time is 1-3 hours.
4. A PET plastic bottle preform according to claim 1, characterized in that: The graphene microsheets have an average radial width of 1-20 μm and an average thickness of 5-25 nm.
5. A PET plastic bottle blank according to claim 1, characterized in that: The compatibilizer is an ethylene-acrylate-glycidyl methacrylate terpolymer; The antioxidant is one or more of antioxidant 168, antioxidant 330, antioxidant 1010, antioxidant 2246, and antioxidant 1035.
6. A PET plastic bottle blank according to claim 1, characterized in that: The antibacterial agent is one or more of nano zinc oxide, nano copper oxide, nano silver, zeolite-loaded zinc, and zeolite-loaded copper; The lubricant is one or more of N,N-ethylene bisstearamide, ethylene bisstearic acid amide, pentaerythritol stearate, and glyceryl stearate.
7. A molding process for a PET plastic bottle blank as claimed in any one of claims 1 to 6, characterized in that: The main steps are as follows: S1, mixing PET resin, PPSU resin, modified graphene microsheets, compatibilizer, antioxidant, antibacterial agent, and lubricant, and drying to obtain a plastic mixture; S2, heating and melting the plastic mixture, extruding and granulating, and obtaining plastic masterbatch; S3, injection molding the plastic masterbatch, cooling and demoulding, to obtain a plastic bottle blank.
Citation Information
Patent Citations
Plastic bottle and bottle blank extrusion process thereof
CN118256070A
FDY (fully drawn yarn) polyester colored yarn and preparation method thereof
CN118621463A